The Food Security of Households Paddy Rice Farmers in Tidal Land Barito Kuala Regency - Hartoni, Hartoni; Shafriani, Karimal Arum (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2023)
This article analyzes the factors that influence the food security of lowland rice farmers' households in tidal land, Barito Kuala Regency. Respondents from this study were 100 rice farmers in tidal land. The analysis for consumption patterns and food security uses descriptive analysis with an approach to the level of adequacy of energy and protein, while for the analysis of factors that affect food security uses a binary logistic regression model. The results showed that the pattern of energy consumption by rice farmers in tidal swamp land was 1,668 calories/capita/day and protein was 48.37 grams/capita/day. The number of farmers who are included in the food security category is 62.00% and 38.00% are not food secure. Households with high food income, small proportion of food expenditure, large availability of food and large area of rice farming land have the opportunity to be more food secure than farmer households on the other hand.